JIHAD, HIJRA, AND MARTYRDOM IN PROPHETIC TRADITIONS: RECLAIMING CONSTRUCTIVE MEANINGS FROM EXTREMIST APPROPRIATION (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article examines the concepts of jihad, hijra (migration), and shahada (martyrdom) as presented in the authentic hadith literature, contrasting their original multidimensional meanings with the reductive and militarized interpretations imposed by extremist movements. These three concepts have been central to the ideological arsenal of radical groups, which have systematically narrowed their semantic range to serve the purposes of recruitment, radicalization, and the justification of violence. Through comprehensive analysis of relevant hadiths in the canonical collections and the interpretive tradition of mainstream Sunni scholarship, this study demonstrates that the authentic prophetic understanding of jihad encompasses personal spiritual struggle, intellectual effort, and social service alongside its martial dimension; that hijra signifies moral transformation rather than mere physical relocation; and that true martyrdom is attained through service to community and ethical living rather than through acts of aggression. The findings provide a hadith-based counter-narrative to extremist ideology and underscore the importance of reclaiming these concepts’ constructive meanings for the contemporary Muslim community.
Keywords: jihad, hijra, martyrdom, shahid, hadith, extremism, counter-narrative, Islamic ethics, radicalization.